2010
DOI: 10.1007/s00787-010-0097-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and measurement influences on heritability estimates in childhood ADHD

Abstract: Twin studies described a strongly heritable component of attention-deficit/hyperactivity disorder (ADHD) in children and adolescents. However, findings varied considerably between studies. In addition, ADHD presents with a high rate of comorbid disorders and associated psychopathology. Therefore, this literature review reports findings from population-based twin studies regarding the influence of subtypes, assessment instruments, rater effects, sex differences, and comorbidity rates on ADHD heritability estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 129 publications
2
64
0
3
Order By: Relevance
“…Notice that the inference raised in this quotation is scientifically wrong: a high heritability does not prove a strong genetic causation because heritability studies cannot disentangle pure genetic effects from gene–environment interactions (Freitag, Rohde, Lempp, & Romanos, 2010; Visscher, Hill, & Wray, 2008). Moreover, estimates of ADHD heritability were strongly influenced by assessment instruments and rating scale (Freitag et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that the inference raised in this quotation is scientifically wrong: a high heritability does not prove a strong genetic causation because heritability studies cannot disentangle pure genetic effects from gene–environment interactions (Freitag, Rohde, Lempp, & Romanos, 2010; Visscher, Hill, & Wray, 2008). Moreover, estimates of ADHD heritability were strongly influenced by assessment instruments and rating scale (Freitag et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, estimates of ADHD heritability were strongly influenced by assessment instruments and rating scale (Freitag et al, 2010). For example, whereas most twin studies using rating scales reported high heritability estimates (60–80%) (Freitag et al, 2010), objective measurements of inattention and impulsivity led to lower estimates (30–36%) (Freitag et al, 2010; Heiser et al, 2006). …”
Section: Resultsmentioning
confidence: 99%
“…For example, the higher co-occurrence of ADHD between monozygotic twins (who share 100% of their genes) compared to their dizygotic counterparts (who share 50% of their genes) cannot rule out the influence of environment, as homozygote twins are often treated more similarly and more often have a physical and psychological closeness than their heterozygotic counterparts (Furman, 2008). Moreover, these studies still depend on observational tools to assess both parent and child behaviour, and the more sophisticated these tools are (and less prone to rater bias), the lower the estimated genetic effect (Freitag, Rohde, Lempp, & Romanos, 2010). Research into the co-occurrence of ADHD in families suffers from extreme difficulty to separate genetic influences from environmental factors (Furman, 2008) that typically run in families such as poverty, parenting style and divorce (Hjern et al, 2010).…”
Section: The Genetic Origins Of Adhd May Be Overestimatedmentioning
confidence: 99%
“…For instance, “the assumption that genetic and environmental influences are independent” (Johnson, Penke, & Spinath, 2011, p. 258) does not hold when genes and environments correlate and interact with each other. Furthermore, the “equal environment assumption”, positing that fraternal and identical twin pairs have similar environments, is often scrutinized, for instance because “twins develop in different types of placental environments” (Freitag, Rohde, Lempp, & Romanos, 2010, p. 314).…”
Section: Introductionmentioning
confidence: 99%